Impact of fixed dental prosthesis on neuroimaging: assessment of artefacts - Syed Murtaza Raza Kazmi; Raima Kaleemi; Wafa Zehra Jamal; Dr Muhammad Azeemuddin; Farhan Raza Khan (Journal of the Pakistan Medical Association)
Objective: To determine the frequency and extent of artefacts in magnetic resonance imaging and/or computed tomography scans of head caused by fixed dental prosthesis.